Regional income inequality in Indonesia: the role of public and private investment - Dani Rahman Hakim,; Iin Rosini, (Penerbit Universiti Kebangsaan Malaysia, 2022)
This study analyzed the effect of investment on regional income inequality in Indonesia using a panel dataset on 33 provinces for the period 2006 -2021. We distinguished among three forms of investment, namely, regional public investment (RDI), private domestic investment (PDI), and foreign direct investment (FDI). By employing a dynamic panel system generalized method of moment (Sys-GMM) estimation, this study revealed that PDI exacerbated regional income inequality Even though PDI alongside FDI positive affect regional economic growth. Among other findings, school participation rate and internet access reduced regional income inequality. But average years of schooling is associated is increased regional inequality suggesting that the school completion benefited middle- and high-income groups. The regional government needs to open up greater access to secondary education and create more proper digital infrastructure in remote areas.